2017
DOI: 10.1007/s00431-017-2996-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical symptoms in very young children assessed for sexual abuse: a mixed method analysis from the ASAC study

Abstract: So far, a recognizable pattern of clinical symptoms for child sexual abuse (CSA), especially in young male children, is lacking. To improve early recognition of CSA, we reviewed physical complaints, physical examination, and tests on sexually transmitted infections (STIs) in confirmed victims (predominantly preschool boys) of CSA from the Amsterdam sexual abuse case (ASAC). We retrospectively analyzed the outcomes of the primary assessment using mixed methods: descriptive analysis of physical complaints, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 27 publications
(36 reference statements)
0
30
0
4
Order By: Relevance
“…The ASAC is unique owing to its large scale, the young age of the victims, the large proportion of boys involved (all abused under similar circumstances), the strong evidence, and the detailed documentation available about the abuse. The current study is part of the larger ASAC study (Lindauer et al, 2014; Vrolijk-Bosschaart et al, 2017a, 2017b). It reports on the first follow-up (T 1 ), carried out in 2013, 3 years after the case was disclosed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASAC is unique owing to its large scale, the young age of the victims, the large proportion of boys involved (all abused under similar circumstances), the strong evidence, and the detailed documentation available about the abuse. The current study is part of the larger ASAC study (Lindauer et al, 2014; Vrolijk-Bosschaart et al, 2017a, 2017b). It reports on the first follow-up (T 1 ), carried out in 2013, 3 years after the case was disclosed.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, studies on CSA outcomes generally focus on older, female victims, because female prevalence rates are higher (Stoltenborgh et al, 2011). The detection of CSA in very young children is also complicated by the absence of CSA-specific signs in most victims (Vrolijk-Bosschaart et al, 2017a). …”
Section: Introductionmentioning
confidence: 99%
“…The only significant finding in this group of children was behavioural difficulties (termed ‘deviant behavioural responses’) noted by the examiners when the children had their genital examination, particularly those who experienced penetrative assault …”
Section: What We Still Do Not Knowmentioning
confidence: 91%
“…In the Amsterdam ASAC study, none of 11 girls confirmed to have been sexually abused, including some with known vaginal penetration, had genital findings considered 'diagnostic' of penetrative abuse when examined months to years later. 34 Furthermore, only 2 of 36 children in this cohort had any history of bleeding -1 had constipation and was known to have experienced anal penetration; in the other child, the origin of the blood loss was unclear. 34 The only significant finding in this group of children was behavioural difficulties (termed 'deviant behavioural responses') noted by the examiners when the children had their genital examination, particularly those who experienced penetrative assault.…”
Section: Genital Findings In the Pre-verbal Childmentioning
confidence: 92%
“…We need to emphasize that CSA-specific findings are only found in a minority of CSA victims (4–5%) when examined over 72 h after the last abuse [1, 2, 21, 22, 38, 49], due to the rapid healing of mucous tissue. Accordingly, in 95%, there are no physical findings at anogenital examination in children examined 48 h or more after the abuse [1, 2].…”
Section: What Makes It So Difficult To Recognize Csa In Children?mentioning
confidence: 99%